Alcohol Use Among Young Adults in Northern California During the COVID-19 Pandemic—An Electronic Health Records-Based Study - Metz, Verena E.; Palzes, Vanessa A.; Chi, Felicia W.; Campbell, Cynthia I.; Sterling, Stacy A. (Frontiers in Psychiatry, 2022)
Background: Individuals globally were affected by the COVID-19 pandemic in myriad of ways, including social isolation and economic hardship, resulting in negative impacts on mental health and substance use. Young adults have been subjected to extraordinary challenges such as job loss, virtual school, or childcare issues, but received limited attention from research. Methods: Using electronic health record data from a large integrated healthcare system in Northern California, this longitudinal observational study examined changes in the prevalence of unhealthy alcohol use (identified via systematic alcohol screening in primary care) from pre- (3/1/2019 – 12/31/2019) to post-COVID onset (3/1/2020 – 12/31/2020) among young adults (18-34 years). Among the 663,111 and 627,095 young adults in the pre- and post-COVID onset periods, 342,889 (51.9%) and 186,711 (29.8%) received alcohol screening, respectively. We fit generalized estimating equation Poisson models to estimate the change in prevalence of unhealthy alcohol use from pre- to post-COVID onset among those who were screened, while using inverse probability weighting to account for potential selection bias of receiving alcohol screening. Heterogeneity in the change of prevalence by patient characteristics was also examined. Results: Overall, the unadjusted prevalence of unhealthy alcohol use slightly decreased from 9.2% pre- to 9.0% post-COVID onset. After adjusting for patient covariates, the prevalence of unhealthy alcohol use decreased by 2% [adjusted prevalence ratio (aPR)=0.98, 95% CI=0.96, 1.00]. The prevalence of unhealthy alcohol use increased among women by 8% (aPR=1.08, 95% CI=1.06, 1.11), patients 18-20 years by 7% (aPR=1.07, 95% CI=1.00, 1.15), and Latino/Hispanic patients by 7% (aPR=1.07, 95% CI=1.03, 1.11). While the prevalence decreased among men by 12% (aPR=0.88, 95% CI=0.86, 0.90), patients 21-34 years by 2% (aPR=0.98, 95% CI=0.96, 0.99), White patients by 3% (95%CI=0.95, 1.00) and patients living in neighborhoods with lowest deprivation indices by 9% (aPR=0.91, 95% CI=0.88, 0.94), their unadjusted prevalence remained higher than their counterparts' post-COVID onset. There was no variation by comorbid mental health conditions or drug use disorders. Conclusions: While changes in unhealthy alcohol use prevalence among young adults were small, findings raise concerns over increased drinking among women, those younger than the U.S. legal drinking age, and Latino/Hispanic patients.